Impaired decision-making in opiate-dependent subjects: Effect of pharmacological therapies - Pirastu, R.; Fais, R.; Messina, M.; Bini, V.; Spiga, S.; Falconieri, D.; Diana, M. (Drug and alcohol dependence, 2006)
Cognitive dysfunction is a major feature of drug addiction. In the present paper, we compared the decision-making ability using the Iowa gambling task of methadone- and buprenorphine-maintained individuals to non opiate-dependent drug-free controls. Buprenorphine-maintained individuals performed better than methadone-maintained individuals, and not differently than non opiate-dependent controls. In addition, methadone-maintained individuals had more perseverative errors on the Wisconsin card sorting task (WCST) as compared with non opiate-dependent drug-free controls whereas buprenorphine-maintained individuals had intermediate scores. Scores on Weschler adult intelligence scale (WAIS-R) were similar for methadone- and buprenorphine-maintained individuals whereas drug-free controls had significantly higher scores. In addition, both opiate-dependent groups performed more poorly than drug-free controls on the Benton visual retention test (BVRT). The results suggest that buprenorphine in contrast to methadone improves decision-making, and thus may be more effective in rehabilitation programs of opiate-dependent subjects and this improvement may be related to its distinct pharmacological action as a k antagonist.